DINAMIKA RESILIENSI PROSES PENGAMBILAN KEPUTUSAN DAN DAMPAKNYA DI KALANGAN REMAJA YANG MENGALAMI KEHAMILAN TIDAK DIINGINKAN - Sujono Riyadi; Sri Handayani (MEDIA ILMU KESEHATAN, 2020)
Background: Unwanted pregnancy is an adversity that provoke a chain reaction in teenager’s life. Teenage unwanted pregnancy culminates to two decision options: whether to keep the pregnancy (until term delivery and thus become a mother to the child, or giving it up for adoption) or to have an abortion. Along the pregnancy, these young girls will face conflicts. Individuals hold potency to overcome conflicts through thinking and resilience skill. Objective: The study aimed to obtain a description of resilience dynamics from the process of decision making to its aftermath and impact in groups of teenage girls experiencing unwanted pregnancy in Special Region of Yogyakarta, Indonesia. Methods: The methodology of this research is a longitudinal qualitative research. Respondents were married and unmarried young women in the Special Region of Yogyakarta who experienced unwanted pregnancies. Results: Firstly, resilience dynamics in continuing pregnancy group showed a course of: a) feeling confused and panic; b) realizing they have done a stupid and embarassing thing; c) confessing their pregnancy honestly; d) doubting whether to continue or to end the pregnancy. Conclusion: Both groups in the first trimester still consider themselves stupid and unable to think in the long term. The advanced pregnancy group and the pregnant women group had a desire to be independent even though they still depended on their parents and felt more challenged to achieve achievements in the second trimester.